Assessing and improving the accuracy of the CPI. (Monthly Labor Review, 2024)
This article provides an overview of the process of estimating the Consumer Price Index (CPI) and examines factors that affect its accuracy, such as data quality, sampling error, bias, and response rates. It discusses new data collection methods and recent improvements to CPI component indexes. The article emphasizes the need for accuracy in the CPI and explores efforts made by the U.S. Bureau of Labor Statistics to improve its precision. The BLS encourages users to use broader indexes for escalation purposes and publishes response rates annually to assist users in judging accuracy. The CPI program uses imputation to handle missing or incomplete responses and addresses potential bias in the index. The BLS updates the CPI market basket annually and introduces new goods and services through various steps. Alternative data sources, such as corporate data and secondary source data, are used to improve the quality and collection of CPI data. The BLS aims to use recent consumer spending to calculate inflation estimates and has updated the CPI spending weights to reduce lag. The BLS continues to work on increasing accuracy and improving timeliness in detecting consumer buying habits. The BLS uses annual Consumer Expenditure surveys and the U.S. Census to monitor changing buying habits and enhance the accuracy, detail, and timeliness of the CPI. Regular revisions and updates are made to improve the methodology and address biases in the CPI.